A drop of water : a book of science and wonder - Wick, Walter (New York : Scholastic, 1997)
Describes the origins, characteristics, and uses of water.
Elem. School Library Collection.
Notable/Best Books (A.L.A.).
Wilson's Children.
5.5
3-6
Keywords: Water -- Juvenile literature; Water; Water